Isotopic Records of Ancient Wildfires in C4 Grasses Preserved in the Sediment of the Ross Sea, Antarctica. Issue 13 (30th June 2022) - Ren, Peng; Luo, Chunle; Zhang, Hongmei; Cui, Chao; Sun, Shuwen; Song, Hongying; Xu, Liping; Rebesco, Michele; De Santis, Laura; Liu, Yanguang; Wang, Xuchen
Abstract: We report carbon isotopic values in total organic carbon (TOC) and pyrogenic carbon (PyC) preserved in two sediment cores from the Ross Sea, Antarctica. The δ 13 C values of PyC ranged from −10.9‰ to −17.2‰, with distinct differences from the δ 13 C values of TOC (−24.1‰ to −26.1‰) in the sediments. The radiocarbon ages of PyC were 9, 128 and 8, 410 years old on average in the two cores but were thousands of years younger than the ages of TOC at the same core depth. These isotopic records provide strong evidence indicating that the PyC was produced from ancient wildfires predominantly in C4 vegetation and transported to Antarctica in the atmosphere. We suggest that ancient wildfires in predominantly C4 grasslands likely frequently occurred on a large scale and at a high intensity in the Southern Hemisphere during the last deglaciation to mid‐Holocene period of 14, 800–4, 200 years ago. Plain Language Summary: A large fraction of pyrogenic carbon (PyC) is produced from incomplete combustion of biomass fires on Earth and is widely distributed on land and in the oceans. This study presents the first evidence of both radiocarbon and stable carbon isotopes in the PyC preserved in the slope sediments of the Ross Sea in Antarctica. The results revealed that PyC accounted for a significant fraction (10.0%–28.0%) of the sedimentary total organic carbon (TOC) buried in the sediments, and both the Δ 14 C and δ 13 C values of PyC showed distinctive differences compared with those of TOC. The well‐defined δ 13 C (−10.9‰ to −17.2‰) and Δ 14 C (−415‰ to −843‰) values of PyC in the sediments revealed that in ancient times, PyC was produced from wildfires of C4 vegetation in the Southern Hemisphere and was transported in the atmosphere to Antarctica. The isotopic records of PyC preserved in the Ross Sea sediments provide meaningful evidence for environmental changes. Key Points: Pyrogenic carbon (PyC) constitutes a significant fraction of total organic carbon (TOC) preserved in sediment of the Ross Sea, Antarctica Distinctive differences in both radiocarbon and stable carbon isotope values exist between PyC and TOC in the Ross Sea sediment The isotopic records indicated that the PyC was produced from ancient wildfires in C4 grasslands and transported to Antarctica in atmosphere